The Conditional Branded Content Analysis of Zara Campaign ‘The Jacket’ - Walid Adriansyah; Fitara A. Tito; Irma Kurniawati; Musbar Afriadi; Nadila Suci Nuria; Retno Wulandari; Septia Wahyu Elda (Graduate School of Communication Universitas Bakrie, 2024)
‘The Jacket’ campaign from the well-known brand Zara raises interesting and controversial dynamics in the fashion industry. Since the launch of this campaign, it has become a significant highlight, creating conversations involving various groups of people and fashion observers. Using the conditional Branded Content Analysis (BCA) method, we analyze the key aspects that made this campaign controversial and how it impacted Zara's brand image. Findings show that the striking jacket design of the campaign is a focal point. Design elements that arouse interest and controversy explain how the aesthetics conveyed in the jacket provide distinguishing characteristics but also become a source of disagreement among consumers and fashion connoisseurs. In the context of marketing strategy, how does Zara design this campaign to attract consumer interest and attraction while being aware of the risks of controversy that may arise? A responsive society is essential in understanding this campaign's impact. We investigated various responses from consumers, fashion observers, and other interested parties. This analysis includes a variety of views, from praise for innovation to criticism of potential insensitivity to specific issues. Combining these views, we provide a comprehensive picture of how The Jacket campaign understands the public consciousness. The broader extent of this controversy impacts Zara's overall brand image by changing consumer perception of the Zara brand and having a long-term impact on the market and customer loyalty. Overall, this study opens a perspective on the controversy behind The Jacket campaign and provides in-depth insight into marketing dynamics in the modern fashion industry.